High-risk patients: modern treatment strategy - D. V. Nebieridze; A. Meliya (Кардиоваскулярная терапия и профилактика, 2010)
This review summarizes modern views on high-risk patients as atherosclerosis-free individuals. The importance of high-risk approach is explained by the fact that this group encompasses the majority of cardiac patients, as well as the majority of cardiovascular events. Therefore, early diagnostics and adequate management of high-risk patients could substantially reduce the incidence of cardiovascular events. The modern treatment strategy for high-risk patients requires pharmaceutical intervention, and has the same principles as the treatment of patients with diagnosed cardiovascular disease. Such components of pharmaceutical treatment as antihypertensive, lipidlowering, and anti-aggregant therapy are discussed in detail.